Epstein–Barr Virus‐Encoded MicroRNA‐BART18‐3p Promotes Colorectal Cancer Progression by Targeting De Novo Lipogenesis - Qingtao Meng; Hao Sun; Shenshen Wu; Giuseppe Familiari; Michela Relucenti; Michael Aschner; Xiaobo Li; Rui Chen (Advanced Science, 2022)
Abstract The Epstein–Barr virus (EBV) genome encodes a cluster of 22 viral microRNAs, called miR‐BamHI‐A rightward transcripts (miR‐BARTs), which are shown to promote the development of cancer. Here, this study reports that EBV‐miR‐BART18‐3p is highly expressed in colorectal cancer (CRC) and is closely associated with the pathological and advanced clinical stages of CRC. Ectopic expression of EBV‐miR‐BART18‐3p leads to increased migration and invasion capacities of CRC cells in vitro and causes tumor metastasis in vivo. Mechanistically, EBV‐miR‐BART18‐3p activates the hypoxia inducible factor 1 subunit alpha/lactate dehydrogenase A axis by targeting Sirtuin, which promotes lactate accumulation and acetyl‐CoA production in CRC cells under hypoxic condition. Increased acetyl‐CoA utilization subsequently leads to histone acetylation of fatty acid synthase and fatty acid synthase‐dependent fat synthesis, which in turn drives de novo lipogenesis. The oncogenic role of EBV‐miR‐BART18‐3p is confirmed in the patient‐derived tumor xenograft mouse model. Altogether, the findings define a novel mechanism of EBV‐miR‐BART18‐3p in CRC development through the lipogenesis pathway and provide a potential clinical intervention target for CRC.